(untitled) (Romano džaniben, 2009)
Ceija Stojka / Meine Wahl zu schreiben – ich kann es nicht Peter Stojka, Rastislav Pivoň / Náš život – Amáro Trajo Lumini,ta Mihai Cioabˇa / Lacrimi Rome / Romane asva Ctibor Nečas / Špalíček romských miniatur Karol Janas / Zabudnuté tábory Kathrin Janka (ed.) / Geraubte Leben Adam Bartosz / Katalog zbiorów cyganologicznych Muzeum okregowego w Tarnowie / Catalogue of The Romany Collections at the District museum in Tarnów Małgorzata Mirga-Tas, Boguslawa Delimata, Krzysztof Gil / Romani Art Valentina Glajar a Domnica Radulescu (eds.) / „Gypsies“ in European Literature and Culture